Does renewable energy redefine geopolitical risks?. (November 2021) - Su, Chi-Wei; Khan, Khalid; Umar, Muhammad; Zhang, Weike
Abstract: For the purpose of this research, we use the rolling window method in order to examine the relationship between global geopolitics risks and renewable energy. The results display a two-way causality between geopolitics risks and renewable energy that are spread across various sub-samples. This shows that geopolitical risks play an important role in the advent of renewable energy primarily because of the energy security, rare metal competition, and trade disputes that are put forth, which stimulate the transition to renewable energy. On the other hand, renewable energy has a significant impact on geopolitical risks that are driven by global economic growth, rising fossil fuels prices and technological innovations. The findings also support the classical production model, which reveals that geopolitical risks and renewable energy have a mutual relationship with one another. Further in this regard, renewable energy is capable of accommodating new powers in the international political system. This aspect is more useful for international peace, and may also reduce geopolitical risks. Therefore, the transition to renewable energy is beneficial to the energy supply and security. Therefore, the governments of the world should encourage the private sector to participate in renewable energy projects, by providing special incentives for this purpose. Highlights: We explore the relationship between global geopolitics risks and renewable energy. The study found the bidirectional causality between variables. The findings support the classical production model. New powers in the international political system can reduce geopolitical risk. Transition to renewable energy is useful for countries' energy supply and security.